(untitled) (The Pakistan Development Review, 1996)
A Field of One’s Own is a pioneering study on gender and property in South Asia. It argues that the gender gap in ’effective’ ownership of property is the ’single most important’ economic factor in explaining gender inequities in South Asia, where land ownership is not only a symbol of economic status but also of social prestige and political power. The author explores the complex, and often unrecognised, reasons for this gender gap and suggests some innovative solutions.